Historical Evolution of Indonesia's Legal System (Transformations Across Different Eras) - Zamroni Abdussamad; Mohamad Hidayat Muhtar; Muhammad Iqbal Mustapa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study analyses the impact of Dutch colonial law on the evolution of the Indonesian legal system following independence, as well as the integration of local and global principles in the establishment of National Legal Policy across several historical periods. The primary issue encountered was the legal duality between Dutch law and customary law, alongside the difficulty of establishing an autonomous national legal system. This study employs normative legal methodologies and a literature-based methodology to examine the progression of legal systems from the colonial era to the reform period. The findings indicated that, although Indonesia's independence, the remnants of colonial law continue to prevail within the legal framework, particularly in civil and criminal domains. Legal reforms initiated in the late 1990s aimed to eliminate colonial influences and include local values with global standards. The difficulty in achieving equilibrium between these two elements remains a significant topic of discussion in Indonesia's legal reform.